Chinese Herbal Medicine Combined With EGFR-TKI in EGFR Mutation-Positive Advanced Pulmonary Adenocarcinoma (CATLA): A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial - Jiao, Lijing; Xu, Jianfang; Sun, Jianli; Chen, Zhiwei; Gong, Yabin; Bi, Ling; Lu, Yan; Yao, Jialin; Zhu, Weirong; Hou, Aihua; Feng, Gaohua; Jia, Yingjie; et al. (Frontiers in Pharmacology, 2019)
Background To determine the clinical activity and safety of Chinese Herbal Medicine(CHM)combined with EGFR-TKI in patients with advanced pulmonary adenocarcinoma (ADC) and the ability of CHM combined with EGFR-TKI to activate EGFR mutations. Methods Three hundred and fifty-four patients were randomly assigned to EGFR-TKI (erlotinib 150 mg/d, gefitinib 250 mg/d, or icotinib 125 mg tid/d) plus CHM (TKI+CHM, N=185) or EGFR-TKI plus placebo (TKI+placebo, N=169). Progression-free survival (PFS) was the primary end point; the secondary end points were overall survival (OS), objective response rate (ORR), disease control rate (DCR), quality of life (FACT-L and LCSS), and safety. Results The median PFS was significantly longer for the TKI+CHM group (13.50 months; 95% CI, 11.20–16.46 months) than with the EGFR-TKI group (10.94 months; 95% CI, 8.97–12.45 months; hazard ratio, 0.68; 95% CI, 0.51–0.90; P=0.0064). The subgroup analyses favored TKI+CHM as a first-line treatment (15.97 vs. 10.97 months, P=0.0447) rather than as a second-line treatment (11.43 vs. 9.23 months, P=0.0530). Patients with exon 19 deletion had a significantly longer PFS than with 21 L858R . The addition of CHM to TKI significantly improved the ORR (64.32% vs. 52.66%, P=0.026) and QoL. Drug-related grade 1-2 adverse events were less common with TKI+CHM. Conclusions TKI+CHM improved PFS when compared with TKI alone in patients with EGFR mutation-positive advanced NSCLC. Trial registration Clinical Trials.gov identifier: NCT01745302.